2014
DOI: 10.1007/s10198-013-0559-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of 11 long-standing health conditions on health-related quality of life using the EQ-5D in a general population sample

Abstract: Objectives Health-related quality of life (HRQoL) measures have been increasingly used in economic evaluations for policy guidance. We investigate the impact of 11 self-reported long-standing health conditions on HRQoL using the EQ-5D in a UK sample.MethodsWe used data from 13,955 patients in the South Yorkshire Cohort study collected between 2010 and 2012 containing the EQ-5D, a preference-based measure. Ordinary least squares (OLS), Tobit and two-part regression analyses were undertaken to estimate the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
1
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 35 publications
7
42
1
8
Order By: Relevance
“…Our results are consistent with those of previous studies in the literature, which have described depression as a major factor, along with chronic diseases, associated with reduced QoL. 9,12,22,23 Population-based surveys 10,11,[23][24][25] using the EQ-5D instrument have detected an impact for diabetes, depression, and respiratory disorders. Even though the impact for respiratory disorders was not significant in the present study, our structured questionnaire included a large spectrum of self-reported respiratory conditions (asthma, bronchitis, or any other respiratory disorder), which could hypothetically explain this difference in relation to other populationbased studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are consistent with those of previous studies in the literature, which have described depression as a major factor, along with chronic diseases, associated with reduced QoL. 9,12,22,23 Population-based surveys 10,11,[23][24][25] using the EQ-5D instrument have detected an impact for diabetes, depression, and respiratory disorders. Even though the impact for respiratory disorders was not significant in the present study, our structured questionnaire included a large spectrum of self-reported respiratory conditions (asthma, bronchitis, or any other respiratory disorder), which could hypothetically explain this difference in relation to other populationbased studies.…”
Section: Discussionsupporting
confidence: 82%
“…25 In terms of sociodemographic characteristics, the associated factors are also consistent with those reported by other studies, reflecting changes in the perception of individuals regarding their HRQoL. 7,9,10,22 For the findings about living in the satellite towns, we could hypothesize that the disparities are enhanced by more precarious urban infrastructure, lower incomes, higher levels of violence, and commuting time, considering that more than half of the residents do not work in the area where they live. 27 One strength of the present study is that the HRQoL of adults living in Brasília was measured by a tool validated for the Brazilian context.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For older people the experience of pain has a considerable impact on autonomy and independence in undertaking activities of daily living (Jakobsson, Hallberg, & Westergren, ); quality of life (Wu et al., ); disability (Eggermont et al., ; Silva, Queiros, Cerqueira, & Rocha, ); activity restriction (Mackichan, Adamson, & Gooberman‐Hill, ); increased morbidity (van Hecke, Torrance, & Smith, ); and mortality (Torrance, Elliott, Lee, & Smith, ). Pain imposes considerable burden on older people, their families and the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients with OA is expected to increase during the coming years in many countries, because life expectancy is also increasing, and OA differentially affects older adults (2). Nevertheless, the burden of OA is related not only to its major impact on lowering quality of life but also to the heavy economic costs associated with the disease in individuals and health care systems (3)(4)(5)(6)(7)(8)(9)(10). Common health care use associated with OA includes office visits, hospitalization, outpatient and inpatient costs, and surgical procedures (e.g., joint replacements).…”
Section: Introductionmentioning
confidence: 99%